2021
DOI: 10.7554/elife.68761
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen αC-subregions critically contribute blood clot fibre growth, mechanical stability, and resistance to fibrinolysis

Abstract: Fibrinogen is essential for blood coagulation. The C-terminus of the fibrinogen α-chain (αC-region) is composed of an αC-domain and αC-connector. Two recombinant fibrinogen variants (α390 and α220) were produced to investigate the role of subregions in modulating clot stability and resistance to lysis. The α390 variant, truncated before the αC-domain, produced clots with a denser structure and thinner fibres. In contrast, the α220 variant, truncated at the start of the αC-connector, produced clots that were po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…57 Since chicken αC regions practically do not have αC-connectors, this observation suggests the important role of the αC-connectors in the fibrin assembly process. A recent study 58 confirmed the importance of the αC-connectors in fibrin assembly and revealed an additional role of the αC regions in this process. Namely, it was shown that the recombinant fibrinogen variant α390, truncated before the αC-domain, produced a clot consisting of thinner fibers making up a denser structural network.…”
Section: Role Of the αC Regions In Fibrin Polymerizationmentioning
confidence: 75%
See 2 more Smart Citations
“…57 Since chicken αC regions practically do not have αC-connectors, this observation suggests the important role of the αC-connectors in the fibrin assembly process. A recent study 58 confirmed the importance of the αC-connectors in fibrin assembly and revealed an additional role of the αC regions in this process. Namely, it was shown that the recombinant fibrinogen variant α390, truncated before the αC-domain, produced a clot consisting of thinner fibers making up a denser structural network.…”
Section: Role Of the αC Regions In Fibrin Polymerizationmentioning
confidence: 75%
“…The stiffness of fibrin clots is substantially increased by interactions between αC regions, and factor XIIIa-catalyzed covalent cross-linking of the α chains contributes further to increased fibrin clot stiffness. 60 A recent study with fibrinogen variant α390, devoid of the αC-domains, which revealed reduced mechanical stability of fibrin clots formed by this variant, 58 further demonstrates the important contribution of the αC-domains to mechanical properties of fibrin clots.…”
Section: Role Of the αC Regions In Mechanical Properties Of Fibrin Clotsmentioning
confidence: 88%
See 1 more Smart Citation
“…The presence of the αC‐region results in thicker fibers by reducing the threshold length of protofibrils for lateral aggregation but it does not change the basic structure of protofibrils, thus the αC‐region likely has a kinetic effect on the lateral assembly of protofibrils 21 . A recent study from our lab found that the absence of the αC‐domain (α390 truncation) leads to thinner, highly branched fibers resulting in reduced clot firmness, whereas abolishing the complete αC‐region including the globular domain and the connector region (α220 truncation) impairs longitudinal growth of protofibrils and results in clots with even lower firmness and a highly abnormal network structure with stunted fibers and a severely reduced resistance to fibrinolysis 29 . Thus, besides the kinetic effect on fibrin assembly and lateral aggregation, the αC‐region has important roles in clot formation including longitudinal fibrin fiber growth and clot stability.…”
Section: Formation Of Protofibrils and Protofibril Packing In Fibrin ...mentioning
confidence: 99%
“…However, bulk measurements show that fibers are not completely straight but straightened by up to 25% shear strain of the whole clot, and fibers only start to align in the direction of stress above 25% shear strain 54,57 . Fibers appear less straight on electron microscopy images than confocal microscopy 29 and fibers appear less straight in uncrosslinked clots 30 …”
Section: Fiber Stretching and Rheologymentioning
confidence: 99%